รูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จในเขตกรุงเทพมหานครและปริมณฑล Integrative Group Counseling Model for the Enhancement of Successful Agingin Bangkok and Suburban - ใจเปี่ยม, วริศรา; เกิดพิทักษ์, ผ่องพรรณ; มาลากุล ณ อยุธยา, ประสาร (Journal of The Royal Thai Army Nurses, 2015)
การวิจัยเรื่องรูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จมีวัตถุประสงค์ 1) เพื่อศึกษาคุณลักษณะการเป็นผู้สูงอายุที่ประสบความสำเร็จ 2) เพื่อพัฒนารูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จ และ 3) เพื่อประเมินประสิทธิผลของการใช้รูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จ กลุ่มตัวอย่างที่ใช้ในการวิจัย แบ่งเป็น 2 กลุ่ม คือ กลุ่มที่ 1 ใช้ในการศึกษาคุณลักษณะการเป็นผู้สูงอายุที่ประสบความสำเร็จ คือ ผู้สูงอายุที่มีอายุระหว่าง 60 - 79 ปี ในจังหวัดกรุงเทพมหานคร และจังหวัดในปริมณฑล จำนวน 400 คน ที่ได้มาจากการสุ่มแบบแบ่งชั้นจากประชากร และกลุ่มที่ 2 คือ ผู้สูงอายุในจังหวัด สมุทรปราการ ที่ได้มาจากการคัดเลือกแบบเฉพาะเจาะจงจากกลุ่มตัวอย่างที่ 1 ที่มีคะแนนการเป็นผู้สูงอายุที่ประสบความสำเร็จตั้งแต่เปอร์เซ็นไทล์ที่ 50 ลงมาและสมัครใจเข้าร่วมการทดลอง จำนวน 20 คน สุ่มเข้ากลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 10 คน กลุ่มทดลองได้รับการให้การปรึกษากลุ่มเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จ ส่วนกลุ่มควบคุมไม่ได้รับการปรึกษาใด ๆ เครื่องมือที่ใช้ในการวิจัย ประกอบด้วย 1) แบบวัดคุณลักษณะการเป็นผู้สูงอายุที่ประสบความสำเร็จ มีค่าความเที่ยงทั้งฉบับ เท่ากับ .89 และวิเคราะห์ความตรงเชิงโครงสร้างของแบบวัดด้วยการวิเคราะห์องค์ประกอบเชิงยืนยัน และ 2) รูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จ มีค่าดัชนีความสอดคล้องอยู่ระหว่าง 0.66 - 1.00 ผลการวิจัย สรุปได้ดังนี้ 1) ค่าเฉลี่ยการเป็นผู้สูงอายุที่ประสบความสำเร็จโดยรวมอยู่ในระดับมาก ส่วนค่าเฉลี่ยรายด้านได้แก่ ด้านร่างกาย จิตใจ และสังคมอยู่ในระดับมาก ส่วนด้านจิตวิญญาณอยู่ในระดับมากที่สุด 2) รูปแบบการให้การปรึกษากลุ่มแบบบูรณาการเพื่อเสริมสร้างการเป็นผู้สูงอายุที่ประสบความสำเร็จ พัฒนาจากการบูรณาการแนวคิด ทฤษฎี และเทคนิคต่างๆ ของการให้การปรึกษากลุ่ม 7 ทฤษฎีประกอบด้วย ทฤษฎีการให้การปรึกษากลุ่มแบบผู้รับบริการเป็นศูนย์กลาง แบบเกสตัลท์ แบบภวนิยม แบบพฤติกรรมนิยม แบบการเล่าเรื่องแบบมุ่งเน้นคำตอบ และการให้การศึกษาทางจิตวิทยา 3) ผู้สูงอายุกลุ่มที่ได้รับการให้การปรึกษากลุ่มแบบบูรณาการมีค่าเฉลี่ยการเป็นผู้สูงอายุพึงพอใจกับการให้การปรึกษา ได้แสดงความคิดความรู้สึก แลกเปลี่ยนความคิดเห็น อภิปรายซักถาม ทำให้ชีวิตเปลี่ยนแปลงในทางที่ดีขึ้น เข้าใจ และยอมรับการเปลี่ยนแปลงต่าง ๆ ของร่างกาย และเห็นความจำเป็นในการดูแลสุขภาพ ภูมิใจในสิ่งที่ตนเองมีอยู่และสามารถถ่ายทอดเรื่องราวต่าง ๆ ให้กับผู้อื่นได้ สามารถจัดการกับอารมณ์ และปล่อยวางได้มากขึ้น ได้ปฏิบัติศาสนกิจและมีสิ่งยึดเหนี่ยวทางจิตใจให้สงบสุข The purposes of this research were 1) to study the successful aging 2) to develop the integrative group counseling model for the enhancement of successful aging, and 3) to evaluate the effectiveness of the integrative group counseling model for the enhancement of successful aging. The sample of the study included 2 groups. The first group of successful aging study consisted of 400 Bangkokian and suburb older person. Those were selected by stratified random sampling from the population. The second group of the study was 20 olderperson from Samut Prakan province whose successful aging score were lower than fiftieth percentile and volunteered to attend the experiment. They were then randomly assigned into two groups, classified as an experiment group and a control group. Each group consisted of 10 older person. The experiment group participated in the integrative group counseling modelwhile the control group did not receive any counseling. The research instruments were 1) a successful aging scale with the reliability coefficient (alpha) of .89 and its construct validity was confirmed through factor analysis and 2) the integrative group counseling model for the enhancement of successful aging with the IOC ranged from 0.66-1.00. The research results were as follows: 1) The total mean score and each dimension scores of successful aging: physiology, psychology, and social were high, while the mean score of the spiritual dimension was the highest. 2) The integrative group counseling model for the enhancement of successful aging was developed from the concepts and techniques of group counseling theories. These group counseling theories were Person-center group counseling, Gestalt group counseling, Existential group counseling, Behavior group counseling, Narrative therapy, Solution focused brief therapy and Psychoeducation. 3) The successful aging of the experimental group after participating in the integrative group counseling model and after the follow-up were significantly higher than before the experiment at .01 level. 4) The successful aging of the experimental group after participating in the integrative group counseling model and after the follow up were significantly higher than that of the control group at .01 level. 5) Focus group report of the experimental group who attended the integrative group counseling model for the enhancement of successful aging after the follow-up showed that they were satisfied with the model. They had a chance to express and share their feelings and ideas during the discussion, for those reasons their lives were improved. They understood and accepted their physical changes and they viewed their health care as necessity. They were proud of themselves and able to transfer their stories to others. They could manage their emotion andcould rest themselves easier. They engaged with the religious activities. Finally, their spirituals were put their souls peacefully.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /> <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />